Random laser emission from a Rhodamine B-doped GPTS/TEOS-derived organic/silica monolithic xerogel - Abegão, Luis M.G.; Manoel, D. S. [UNESP]; Otuka, A. J.G.; Ferreira, P. H.D.; Vollet, D. R. [UNESP]; Donatti, D. A. [UNESP]; De Boni, L.; Mendona, C. R.; De Vicente, F. S. [UNESP]; Rodrigues, J. J.; Alencar, M. A.R.C. (IOP Publishing, 2017)
A Rhodamine B-doped 3-glycidoxypropyltrimethoxysilane (GPTS)/tetraethyl orthosilicate (TEOS)-derived organic/silica monolithic xerogel with excellent optical properties was prepared and its potential as a random laser host investigated. This hybrid material has a non-porous organic/inorganic morphology with silica-rich nanoparticles of less than 10 nm in diameter homogeneously dispersed within the matrix. Random laser emission with incoherent feedback, centered at 618 nm, was observed from Rhodamine B incorporated into the monolithic xerogel when excited by a 532 nm pulsed laser. This hybrid system is shown to be very promising for the development of a new class of random laser-based integrated devices, with applications ranging from optical bio-imaging to sensing.
Keywords: incoherent feedback; organic-inorganic hybrid material; random laser; silica nanoparticles